Compound 4f, a novel brain-penetrant reversible monoacylglycerol inhibitor, ameliorates neuroinflammation, neuronal cell loss, and cognitive impairment in mice with kainic acid-induced neurodegeneration. - Naoto Arimura; Chie Maeda; Kazunobu Aoyama; Namiko Yamaguchi; Ayumu Sugiura; Yasuko Takahashi; Ryouta Maeda; Tatsuya Ando; Makoto Kamata; Hideki Matsui; Maiko Tanaka (PLoS ONE)
Neuroinflammation, a hallmark of neurodegenerative diseases, is associated with neuronal cell loss and cognitive dysfunction. Monoacylglycerol lipase (MAGL) is involved in neuroinflammation in the brain via the degradation of endocannabinoid 2-arachidonoylglycerol to arachidonic acid, a precursor of some eicosanoids; therefore, MAGL inhibitors are expected to have anti-inflammatory effects. We recently developed a reversible, selective, central nervous system penetrant, and orally available MAGL inhibitor, compound 4f. Compound 4f (1 mg/kg) robustly increased 2-arachidonoylglycerol levels and decreased arachidonic acid levels in the mouse brain. To examine whether compound 4f can suppress neuroinflammation and neuronal cell loss, kainic acid (KA)-injected mice were used as a neuroinflammation model in this study. Compound 4f (1 mg/kg) significantly decreased the cytokine and chemokine expression levels and suppressed neuronal cell loss in the hippocampi of mice. Compound 4f also ameliorated cognitive impairment in KA-injected mice. The cannabinoid receptor 1 antagonist, AM251, and cannabinoid receptor 2 antagonist, AM630, partly blocked the neuroprotective effects of compound 4f in the hippocampi of KA-injected mice. Gene expression profiles and pathway analyses revealed that compound 4f reversed the KA-induced changes in the expression of genes related to inflammation and neurotransmission. These results indicate that the selective and reversible MAGL inhibitor, compound 4f, can be used as a potential therapeutic agent for the treatment of neurodegenerative diseases.